Second-Generation Long-Acting Injectable Antipsychotics and the Risk of Treatment Failure in a Population-Based Cohort - Janzen, Donica; Bolton, James M.; Leong, Christine; Kuo, I fan; Alessi-Severini, Silvia (Frontiers in Pharmacology, 2022)
Introduction Second-generation long-acting injectable antipsychotics (SG-LAIAs) may improve outcomes relative to other antipsychotics. Real-world studies using linked administrative databases play an important role in assessing comparative effectiveness of antipsychotic medications. Methods We used a prevalent new user design in a population-based cohort of antipsychotic users with a diagnosis of psychotic disorder to compare primary outcome of treatment failure, defined as psychiatric hospitalization, completed suicide, incarceration or treatment discontinuation. Additional outcomes were all-cause mortality. SG-LAIA users were matched 1:1 with other antipsychotic users based on time-conditional propensity score, calendar time, and prior antipsychotic exposure. Results Use of LAIAs was not associated with lower risk of treatment failure compared to other antipsychotics (adjusted hazard ratio 1.07, 95% confidence interval 0.98-1.15), but did reduce all-cause mortality (adjusted hazard ratio 0.69, 95% confidence interval 0.48-0.99). Monotherapy with LAIAs was superior to other antipsychotic monotherapy (adjusted hazard ratio for treatment failure 0.83, 95% confidence interval 0.78-0.89), and LAIAs were superior to other antipsychotics in antipsychotic-naïve users (adjusted hazard ratio for treatment failure 0.57, 95% confidence interval 0.47-0.70). Conclusion In this population-based cohort, SG-LAIAs reduced risk of treatment failure in incident new users, but not in prevalent new users.